DYNAMICS OF EEG WOMEN DURING THE OVARIAN-MENSTRUAL CYCLE (OMC) - Margarita Gennad’evna Vodolazhskaya; Inna Nikolaevna Chadova (Вестник Северо-Кавказского федерального университета, 2022)
Dynamics of EEG indicators of women in preovulation (the I stage) and pastovulation periods (the II stage) OMC is researched. Higher values of sizes of amplitude and average power rhythms EEG in Ist phase OMC in comparison with IInd stage are established, recorded, in right hemisphere.